2021
DOI: 10.35445/alishlah.v13i3.809
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Thai English: Indonesian Pre-service Teachers Lenses During Teaching Practicum in Thailand

Abstract: Over the last few decades, World Englishes have shifted the paradigm of how both native and non-native speakers view English as a lingua franca. This paradigmatic shift has attracted scholars to conduct a plethora of investigations on the roles of English as an international language. However, scrutinizing the pre-service teachers’ attitudes towards Thai English amid their teaching practicum in Thailand remains under-explored, notably viewed from Indonesian perspectives. This study investigated Indonesian pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Excerpt 5 The experience of P3 (third participant) pointed that through CL, he can freely ask for help to other group members. The data showed CL disclosed wide opportunities for all students from different abilities to improve their performance and get better learning outcomes (Fauziyah et al, 2021). As cited by Leasa and Corebima (2017, p. 2), Pham affirmed that CL allows high and low ability students to motivate and help each other which directs them to improve their academic performances.…”
Section: Positive Interdependence and Group Processingmentioning
confidence: 77%
“…Excerpt 5 The experience of P3 (third participant) pointed that through CL, he can freely ask for help to other group members. The data showed CL disclosed wide opportunities for all students from different abilities to improve their performance and get better learning outcomes (Fauziyah et al, 2021). As cited by Leasa and Corebima (2017, p. 2), Pham affirmed that CL allows high and low ability students to motivate and help each other which directs them to improve their academic performances.…”
Section: Positive Interdependence and Group Processingmentioning
confidence: 77%
“…TSA has been utilized by many academics in Indonesia to determine the standards that children attending vocational high schools need to meet. Fauziyah et al (2021) carried out research in Tasikmalaya and discovered that the perceived English needs identified by participants included being a hotel employee with English communication competency and being a good communicator with a service attitude. This finding indicates that the ultimate purposes in teaching English program are appropriate already based on the target situation of the hospitality industry.…”
Section: Implementation Of Tsa Between Indonesia and Other Asian Coun...mentioning
confidence: 99%